2017
DOI: 10.5530/jscires.6.2.16
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Linguistics Publications in the Web of Science

Abstract: This article investigates the world's publications in the category of linguistics based on Thomson Reuters' Social Science Citation Index (SCCI) from 2005-2014. Research achievements were recorded and analyzed, including publication year, characteristics of journals, productivity of authors, institutions, and countries, publication years, citation life of highly cited articles. Results found that while the number of publications dramatically increased, the average number of authors, cited references, and count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Some studies analyzed research fields such as RFID' publications (de Oliveira et al, 2019); tuberculosis (Nafade et al, 2018); lncRNA (Zhai et al, 2018); urban education (Liang & Wang, 2018); environmental damage (Li et al, 2018); linguistics (Mohsen et al, 2017); information architecture (Taga et al, 2017); fuzzy research (Merigó et al, 2015); welding (Layus and Kah, 2015); computer science (Uddin et al, 2015); and entrepreneurship (Landström et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies analyzed research fields such as RFID' publications (de Oliveira et al, 2019); tuberculosis (Nafade et al, 2018); lncRNA (Zhai et al, 2018); urban education (Liang & Wang, 2018); environmental damage (Li et al, 2018); linguistics (Mohsen et al, 2017); information architecture (Taga et al, 2017); fuzzy research (Merigó et al, 2015); welding (Layus and Kah, 2015); computer science (Uddin et al, 2015); and entrepreneurship (Landström et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent decades have seen a drastic increase in the use of quantitative techniques in linguistics, to the extent that Janda (2013) speaks of 'the quantitative turn'. Indeed, textbooks on quantitative methodology such as Baayen (2008a), Gries (2013), Levshina (2015), and Winter (2019) are among the best-selling in the field, and a bibliometric investigation of linguistic journals for the period 2005-2014 (Mohsen et al, 2017) revealed that the two most cited articles were decidedly quantitative in their approach and dealt with the application of mixed-models to the investigation of language (Baayen et al, 2008b;Jaeger, 2008). Though some subfields have been more reluctant in embracing this trend, hardly any subfield has remained completely untouched, and historical linguistics is no exception.…”
Section: Inferential Statistics With the Variable Timementioning
confidence: 99%
“…For instance, Lei and Liu (2018) conducted a study which covers 42 journals of applied linguistics mentioned in the Social Science Citation Index (SSCI). Mohsen et al (2017) conducted a study on linguistic publications which appeared during the years 2005-2014 and which were included in the Thomson Reuters' Social Science Citation Index (SSCI). Arik (2015) reviewed the articles published during 1900-2013 and mentioned in the Social Science Citation Index (SSCI), and discussed the characteristics of the linguistic articles included in the Arts and Humanities Citation Index (A and HCI) between 1975 and 2013.…”
Section: Bibliometricsmentioning
confidence: 99%